An investigation into literacy development in Grade 4 English and isiXhosa home language textbooks : a comparative study - Fulani, Ntombekhaya Cynthia (Rhodes University, Faculty of Education, Department of Education, 2015)
The 2006 Progress in International Reading Literacy Study (PIRLS) painted a gloomy picture of South African literacy when South Africa came last out of 40 countries. It was from this background that my study set out to investigate two English and two isiXhosa grade 4 home language textbooks with their accompanying teachers' guides from two publishing houses, together with the home language curriculum documents for English and Xhosa because they are an important component in literacy development. It is important to emphasise that this study examined textbooks, not how teachers mediate such textbooks in their classrooms. In other words, my focus was on the textbooks themselves, and it was primarily through textual analysis of this stable, readily available data that I have been able to compare and analyse the potential they offer learners and teachers to achieve the literacy goals prescribed by the curriculum. The study also investigated the likelihood of differential attainment for learners as a result of using these textbooks. This was done by looking at whether the textbooks were in line with the literacy outcomes for English and isiXhosa home languages. It also looked at the kind of reader/writer envisaged in the selected textbooks and the level of challenge the selected textbooks offer and how, if at all, learners are encouraged to be critical readers and writers. The findings of the study were that the English and isiXhosa textbooks of each publishing house envisaged different learners. The English textbooks envisaged a cosmopolitan learner who has greater access to academic literacy. While the isiXhosa textbooks envisaged a parochial learner who has less access to academic literacy compared to the English learner
Keywords: Progress in International Reading Literacy Study; Literacy -- South Africa; Textbooks -- South Africa -- Criticism, Textual; English language -- Study and teaching (Elementary); Xhosa language -- Study and teaching (Elementary)